Highly sensitive capacitive cell based on a novel CuTsPc-TiO2 nanocomposite electrolytic solution for low-temperature sensing applications - Abdullah, Shahino Mah; Rafique, Saqib; Hamdan, Khairus Syifa; Roslan, Nur Adilah; Li, Lijie; Sulaiman, Khaulah (Elsevier, 2019)
This work demonstrates a highly efficient electrochemical cell based on the hybrid nanofluid of titanium dioxide (TiO 2 ) nanoparticles dispersed in a water-based copper (II) phthalocyanine-tetrasulfonic acid tetrasodium salt (CuTsPc) solution. A chemical cell of ITO/nanofluid/ITO has been fabricated to study the effect of temperature variations towards its capacitance and resistance. The resultant device showed capacitive sensing mechanism, and the synergistic hybridization of the two different sensing elements lead to the superior performance as compared to the single CuTsPc based device. The hybrid device outperformed the pristine CuTsPc based device in terms of sensitivity, stability, linearity, response/recovery and possessed narrow hysteresis loop. © 2019 Elsevier B.V.